Efficacy and cost effectiveness of telemedicine for improving access to care in the Paris region: study protocols for eight trials. Issue 1 (December 2015) - Charrier, Nathanael; Zarca, Kevin; Durand-Zaleski, Isabelle; Calinaud, Christine
Abstract Background With the development of information and communication technologies, telemedicine has been proposed as a way to improve patient management by facilitating access to appropriate diagnosis and treatment. The Paris Ile de France Regional Health Agency is currently funding a comprehensive program of telemedicine experiments. This article describes the protocols for the evaluation of the implementation of telemedicine in the Paris region. Methods/design Over 2, 500 patients have been included in eight studies addressing the use of telemedicine in the context of specific diseases or settings. Two projects are randomized controlled trials, while the six other projects are based on before-after designs (differences in differences studies). Based on the MAST model and the French national framework, we identified endpoints to assess the impact of telemedicine on five dimensions: clinical effectiveness, cost-effectiveness, security of the application, patient satisfaction and quality of life and perception of professionals. Discussion Telemedicine encompasses a wide range of services and stakeholders, and thus study protocols must be tailored to the specific constraints and interests of the users. Trial registration NCT02110433 (03/07/2014), NCT02157740 (05/27/2014), NCT02374697 (02/05/2015), NCT02157727 (05/27/2014), NCT02229279 (08/28/2014), NCT02368769 (02/05/2015), NCT02164747 (NCT02164747), NCT02309905 (11/27/2014).